DIALOG ANTAR-IMAN SEBAGAI RESOLUSI KONFLIK TAWARAN MOHAMMED ABU-NIMER - Akhmad Rizqon Khamami (AL-TAHRIR, 2014)
Abstract: Many are doubt about the roles of religion in maintaining peace, accusing it even as a source of conflicts. However, others attempt to prove that religion can become a peace keeper. In Islam, this idea comes from Mohammed Abu Nimer. This article examines Abu Nimer’s ideas of non-violence approaches to conflict resolution. It explores his non-violence initiatives in peace building and analyzes his arguments for conflict resolution and the necessity of interfaith dialogue. To him, interfaith dialogue is a medium through which world peace amongst religious communities can be established. It is only and through dialogue that people can avoid having hostilities and violent conflict in the name of religion. This article argues that Abu Nimer’s method can be classified into communicative pluralism that combines particularist views and universalist views. His approaches to peace building and conflict resolution feature unique concepts that differ from other interfaith activists.